Bacteriological Profile of Neonatal Sepsis and Antibiogram of the Isolates - Parajuli, Roshan; Pant, Narayan Dutt; Bhandari, Raju; Giri, Anil; Rai, Suman; Acharya, Ganesh Prasad; Shah, Pradeep Kumar (Journal of Nepal Paediatric Society, 2017)
Introduction: Neonatal sepsis is a serious problem in developing countries like Nepal. The main objectives of this study were to determine the bacteriological profile of neonatal sepsis, to determine the antimicrobial susceptibility patterns of the causative agents and to evaluate the association between the neonatal sepsis and the different characteristics of the neonates. Methods: A hospital based cross-sectional study was conducted among a total of 450 neonates suspected of suffering from sepsis. Blood culture was performed using statdard microbiological techniques. The colonies grown were identified on the basis of colony morphology, Gram’s stain and biochemical tests. The antimicrobial susceptiblility testing was performed by Kirby Bauer disc diffusion method. Results: Out of total 450 blood samples, 92 (20.4%) were culture positive. Of which, 16 (17.4%) samples contained gram negative bacteria and 76 (82.6%) samples contained gram positive cocci. The most common bacterial pathogens isolated were Staphylococcus epidermidis (67.4%) followed by Escherichia coli (13%). All gram positive cocci were susceptible to vancomycin, while all gram negative bacilli were sensitive to amikacin. There was statistically significant relationship between neonatal sepsis and gestation age of neonates. Conclusions: Neonatal sepsis is still present as a serious problem in Nepal. Staphylococcus epidermidis was the most common cause of the neonatal sepsis. Prematurely delivered neonates should be given more care, as they are more prone to suffering from neonatal sepsis. Vancomycin and amikacin can be used as the drugs of choice for preliminary treatment of neonatal sepsis in our settings.